Analisis Cacat Informed Consent dalam Praktik Kedokteran dan Implikasinya terhadap Pertanggungjawaban Hukum Tenaga Medis dalam Perspektif Hukum Kesehatan Indonesia - Cecep Kholik Suparman; Wahyudi W (Media Hukum Indonesia (MHI), 2026)
Informed consent is a fundamental principle in healthcare services, demonstrating respect for patient autonomy and legal protection for medical personnel. However, in practice, informed consent is often not implemented optimally, resulting in legal flaws that have implications for the accountability of medical personnel. This study aims to analyze the forms of flaws in informed consent and their implications for the legal accountability of medical personnel from the perspective of Indonesian health law. The research method uses a normative juridical approach through a literature review of laws and legal literature, by analyzing the Criminal Code, the Health Law, the Medical Practice Law, and related medical regulations. The results show that flaws in informed consent include lack of information, misunderstanding, coercion, deception, and patient incompetence. These flaws in informed consent have implications for civil liability based on unlawful acts and breach of contract, criminal liability through articles on assault and fraud, and administrative and ethical liability through the MKDKI and MKEK. Strengthening informed consent requires a multilevel approach that includes policy harmonization, improved education of healthcare personnel, utilization of technology, patient empowerment, and consistent law enforcement to provide balanced protection for patients and medical personnel.